Inhibitory effects of methyl-3, 5-di-O-caffeoyl-epi-quinate on RANKL-induced osteoclast differentiation. Issue 10 (1st June 2018) - Kim, Tae Hoon; Ihn, Hye Jung; Kim, Kiryeong; Cho, Hye-Sung; Shin, Hong-In; Bae, Yong Chul; Park, Eui Kyun
Graphical abstract: Abstract: In this study, we have shown that methyl-3, 5-di- O -caffeoyl- epi -quinate, a naturally occurring compound isolated from Ainsliaea acerifolia, inhibits receptor activator of nuclear factor-κB ligand (RANKL)-induced formation of multinucleated tartrate-resistant acid phosphatase (TRAP)-positive osteoclasts and the expression of osteoclast marker genes. Methyl-3, 5-di- O -caffeoyl- epi -quinate also inhibited RANKL-induced activation of p38, Akt and extracellular signal-regulated kinase (ERK) as well as the expression of nuclear factor of activated T -cell (NFATc1), the key regulator of osteoclast differentiation. Negative regulators for osteoclast differentiation was upregulated by methyl-3, 5-di- O -caffeoyl- epi -quinate. Collectively, our results suggested that methyl-3, 5-di- O -caffeoyl- epi -quinate suppresses osteoclast differentiation via downregulation of RANK signaling pathways and NFATc1.